2021
DOI: 10.3390/rs13193929
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Satellite Precipitation Estimates over the South West Pacific Region

Abstract: Rainfall estimation over the Pacific region is difficult due to the large distances between rain gauges and the high convection nature of many rainfall events. This study evaluates space-based rainfall observations over the South West Pacific Region from the Japan Aerospace Exploration Agency’s (JAXA) Global Satellite Mapping of Precipitation (GSMaP), the USA National Oceanographic and Atmospheric Administration’s (NOAA) Climate Prediction Center morphing technique (CMORPH), the Climate Hazards group Infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…A comprehensive analysis of the SWCEM satellite precipitation data performed over Australia showed that blended satellite-gauge products had higher correlations and smaller errors than gauge analysis [48][49][50][51][52][53]. Similarly, earlier studies demonstrated the usefulness of satellite precipitation data not only for Australia but also for countries in the Pacific region [54,55], which means that the SWCEM data as well as the developed in this study flood risk assessment methodology could potentially be used in other countries in the Asia-Pacific region.…”
Section: Flood Hazard Indicators and Data Collectionsupporting
confidence: 59%
“…A comprehensive analysis of the SWCEM satellite precipitation data performed over Australia showed that blended satellite-gauge products had higher correlations and smaller errors than gauge analysis [48][49][50][51][52][53]. Similarly, earlier studies demonstrated the usefulness of satellite precipitation data not only for Australia but also for countries in the Pacific region [54,55], which means that the SWCEM data as well as the developed in this study flood risk assessment methodology could potentially be used in other countries in the Asia-Pacific region.…”
Section: Flood Hazard Indicators and Data Collectionsupporting
confidence: 59%
“…Traditional ground-based instruments (weather stations and radars) are considered as the most reliable sources of precipitation measurements [2]. However, the main difficulties in accessing the uninterrupted measurements of precipitation for many applications in mountainous and remote areas are the rugged topography and an inequitable distribution of weather stations [3][4][5][6]. The Himalayan Mountains also have similar constraints on obtaining precipitation data due to sparse or non-uniform installation of meteorological stations.…”
Section: Introductionmentioning
confidence: 99%
“…To aid, prepare and warn communities of drought, the operational implementation of satellite monitoring rainfall products is becoming more commonplace in the Pacific region as remote-sensing research progresses [15][16][17][18]. Yet, satellite SM evaluation is a relatively under-explored research space, owing to the minimal-to-none in situ SM stations or water balance models that can be used to evaluate satellite SM products in the Pacific region.…”
Section: Introductionmentioning
confidence: 99%